2022
DOI: 10.3389/fsurg.2022.985034
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value and immunological role of BAIAP2L2 in liver hepatocellular carcinoma: A pan-cancer analysis

Abstract: BackgroundIn recent years, the role of BAI1-associated protein 2-like 2 (BAIAP2L2) in the prognosis and immune microenvironment of various cancers has attracted increasing attention. However, its clinical value and immune infiltration in liver hepatocellular carcinoma (LIHC) remain unclear.ObjectiveTo investigate the prognostic value of BAIAP2L2 and its correlation with immune infiltration in LIHC, we conducted corresponding data mining.MethodsIn this study, The Cancer Genome Atlas, GTEx, StarBase, UALCAN, TIM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…BAIAP2L2 was also upregulated in Epi_1, Epi_2, Epi_3, Epi_4 (Supporting Information: Table ). This gene was found to be active in cervical squamous cell carcinoma, with high‐level expression indicative of unfavorable overall survival in patients with this carcinoma 60 . Although there is no direct association linking CAV1 with cervical cancer, DNA viruses, including HPV16, John Cunningham virus, and bovine papillomavirus type 1 (BPV1), have been found to enter host cells through clathrin‐mediated endocytosis and CAV1‐1‐dependent pathways 61 .…”
Section: Resultsmentioning
confidence: 99%
“…BAIAP2L2 was also upregulated in Epi_1, Epi_2, Epi_3, Epi_4 (Supporting Information: Table ). This gene was found to be active in cervical squamous cell carcinoma, with high‐level expression indicative of unfavorable overall survival in patients with this carcinoma 60 . Although there is no direct association linking CAV1 with cervical cancer, DNA viruses, including HPV16, John Cunningham virus, and bovine papillomavirus type 1 (BPV1), have been found to enter host cells through clathrin‐mediated endocytosis and CAV1‐1‐dependent pathways 61 .…”
Section: Resultsmentioning
confidence: 99%
“…Tumor-infiltrating immune cells within the tumor microenvironment can predict the prognosis of cancer patients 19 . It has been shown that BAIAP2L2 may have immunological value in HCC 20 . Previous studies have identified a crucial role of cuprotosis in tumor prognosis and tumor immune microenvironment 21 , 22 .…”
Section: Introductionmentioning
confidence: 99%